Interspecific hybridization of Dendrobium mirbelianum x D. nindii or D. discolor, in vitro seed germination, seedling growth and plantlet acclimatization - DESI MAULIDA; YUSNITA YUSNITA; DWI HAPSORO; AGUSTIANSYAH AGUSTIANSYAH; AGUS KARYANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Maulida D, Yusnita Y, Hapsoro D, Agustiansyah A, Karyanto A. 2023. Interspecific hybridization of Dendrobium mirbelianum x D. nindii or D. discolor, in vitro seed germination, seedling growth and plantlet acclimatization. Biodiversitas 24: 3004-3011. Dendrobium mirbelianum Gaudich. (P1), D. nindii W.Hill (P2), and D. discolor Lindl. (P3) as a parent crossing are potentially resulting a new type of orchid as the novel breeding achievement. This study aimed to identify orchid crossing compatibility and evaluate the most effective and efficient media for hybrid seed germination and growth. The study consisted of three experiments, namely interspecific hybridization (experiment 1), in vitro hybrid seed germination (experiment 2), and in vitro growth of the hybrid seedlings (experiment 3). The first experiment was conducted by a simple modified line×tester mating design, and all experiments used a completely randomized design, with five replications in the first experiment and three replications in the second and third experiments. The first experiment presented all of the crossing emerging seed pods, but only hybrid seeds from cross D. mirbelianum x D. nindii and its reciprocal cross that potent to germinate in all tested media as the second experiment result. The third experiment showed FF+tryptone was the best media indicated by the highest and heaviest seedling after 8 months after sowing. All of the crossings resulted seed pods, however, only D. mirbelianum x D. nindii and its reciprocal cross that able to germinate in all tested media. Foliar fertilizer is the most recommended media for germinating hybrid orchid seeds, and FF+tryptone is the best for seedling growth.